A Study on the Relationship between Social Support and Subjective Well being of Vocational College Students - LU, JIHU (Pacific International Journal, 2024)
The objective of this research is to examine the correlation between social support and subjective well-being among vocational college students using empirical surveys. The intention is to provide a foundation for increasing their mental health and improving their subjective well-being. A total of 375 students from vocational colleges were chosen as participants, and their levels of social support and subjective well-being were assessed by the administration of a questionnaire. The findings indicated a substantial positive correlation between subjective well-being and objective support, subjective support, usage of support, and the overall social support score. (2) Female vocational college students exhibit a notably greater degree of assistance use compared to their male counterparts. There exists a notable disparity in survival rates between students pursuing liberal arts and those studying science in terms of subjective well-being, with science students exhibiting much greater levels of subjective well-being compared to liberal arts students. There are notable variations seen across different grades in terms of objective support, subjective support, usage of support, overall social support score, and subjective well-being. Following the LSD post-test analysis, it was determined that freshman students exhibited significantly lower levels of objective support, subjective support, total social support score, and subjective well-being score compared to students in other grades. On the other hand, sophomore students scored significantly higher than students in other grades in terms of utilization of support. (3) A multiple regression analysis revealed that objective support, subjective support, and usage of support positively predict subjective well-being. This research examines the correlation between social support and subjective well-being and offers empirical evidence and theoretical direction to enhance the subjective well-being of vocational college students via more focused coaching.